Benjamina Franklina Izmišljena naprava za upravljanje svojega življenja - Franklin, Benjamin, filozof
Usp. Franklin, B. Autobiography, part II (It was about this time I conceiv'd the bold and ardouous project of arriving at moral perfection ...)